2016
DOI: 10.1080/00913847.2016.1216239
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on ACL reconstruction: a systematic review

Abstract: Therapeutic Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…The results of this review regarding the effect of smoking on tendons are consistent with the findings reported in a previous systematic review by Bishop et al [ 16 ]. For ligaments, smoking was associated with poor functional and stability scores after ACL reconstruction, consistent with the findings in systematic reviews by Kanneganti et al [ 13 ] and Novikov et al [ 14 ] that reported negative effects of smoking on postoperative outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this review regarding the effect of smoking on tendons are consistent with the findings reported in a previous systematic review by Bishop et al [ 16 ]. For ligaments, smoking was associated with poor functional and stability scores after ACL reconstruction, consistent with the findings in systematic reviews by Kanneganti et al [ 13 ] and Novikov et al [ 14 ] that reported negative effects of smoking on postoperative outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Another systematic review revealed an association between smoking and lumbar disc herniation [ 12 ]. Three other reviews found smoking was related to negative postoperative outcomes on knee ligaments [ 13 ], higher complication rates after anterior cruciate ligament (ACL) reconstruction [ 14 ], and slowed healing of rotator cuff repair [ 15 ]. Also, one review found smoking was associated with rotator cuff tears and other shoulder symptoms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The natural prognosis is inversely related to vulnerability as the risk factors that contributed to the occurrence of adverse outcomes are generally still in place (e.g. recovery rates of smokers vs. non-smokers differ [25–26]). At the same time, vulnerable individuals are a challenge in professional care as they require complex and often interdisciplinary case management [27] and dropout rates are high [28].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of 17 studies indicated that smoking was associated with significantly worse clinical outcome scores, an increased anterior translation (2.68 mm in smokers vs. 1.89 mm in non-smokers), and increased postoperative complication rates (infection and venous thromboembolism) after anterior cruciate ligament (ACL) reconstruction. 44 A national insurance database of 13,358 patients showed smokers had higher infection rate (2.0% vs. 0.9%; OR, 2.3, p < 0.001), higher incidence of venous thromboembolism (1.0% vs. 0.5%; OR, 1.9; p ¼ 0.035), and higher rate of subsequent ipsilateral or contralateral ACL reconstruction (12.6% vs. 7.8%; OR. 1.7; p < 0.001; level of evidence, III).…”
Section: Worse Outcomes After Surgery On Tendon and Ligament Surgerymentioning
confidence: 99%